ANALISIS KELAYAKAN USAHA TERNAK LEBAH MADU JAYA MAKMUR DI DESA JONO OGE KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Arifuddin Lamusa,Afandi, Moh. Romi Wardoyo (AGROTEKBIS, 2016)
The research aim was to determine income and feasibility of honey bee farming of Jaya Makmur for one production period. The research location was purposively selected with the consideration that Jaya Makmur is the only bee farming in Sigi and registered in Forest Office of Central Sulawesi. The research was carried out during one production period in April-June 2015. Respondents in this study were the leader and three employees of the bee farming. Research data was analyzed descriptively and using income and feasibility analysis. The research results showed that the business of the honey bee farming generated income of IDR 3,899,510 for one production period. Cost revenue ratio (R/C) obtained was 1.27 suggesting that the business of the bee farming is feasible to be developed in Jono Oge, Sigi Biromaru of Sigi District.